Relationship between Corporate Governance Practices and Credit Risk in Banking - Mutua, Hellen (International Journal of Modern Risk Management, 2023)
Purpose: The aim of the study was to investigate Relationship between Corporate Governance Practices and Credit Risk in Banking. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings:The findings indicated a significant correlation between effective corporate governance practices and lower levels of credit risk exposure within banks. Specifically, banks that exhibited robust governance mechanisms, including independent board oversight, transparent risk management frameworks, and strong internal controls, demonstrated reduced instances of credit defaults and non-performing loans. These findings collectively underscored the pivotal role of corporate governance in mitigating credit risk and enhancing the overall stability and resilience of banking institutions. Unique Contribution to Theory, Practice and Policy: Agency Theory, Stakeholder Theory and Pecking Order Theory may be used to anchor future studies on relationship between corporate governance practices and credit risk in banking. Banks should prioritize recruiting directors with diverse skill sets, including expertise in risk management, to serve on their boards. Regulators should impose stricter disclosure requirements for banks' credit risk exposure and management practices.